Penguatan Budaya Literasi di Pondok Pesantren El Karim Cibuah Warunggunung Lebak Banten Melalui Gerakan Literasi - Hendrieta Ferieka; Ahmad Habibi Syahid; Falikh Alhaq (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2023)
Banten as a province, is also known as an area with the nickname " Seribu Kyai Sejuta Santri". The nickname is inseparable from the reality of the existence of Islamic boarding schools that are growing in large numbers in the province of Banten. Starting from traditional boarding schools to modern boarding schools. Pesantren is an institution that provides religious education services. On the Pondok Pesantren Database page released by the Directorate of Islamic Boarding School Education (DITPDPONTREN), the Ministry of Religion, R.I. it is stated that the total number of pesantren in Banten province is 4,579 pesantren. Pesantren not only teach religious education but also life education so that students are able to become independent individuals when they leave the pesantren. As mentioned earlier, the existence of many Islamic boarding schools and the activeness of these institutions in providing religious education services has a linear line with the religious pattern of the people who are known to be religious fanatics. Even so, this linear line does not apply to literacy and writing cultures. Therefore, community service activities through strengthening literacy culture among students need to be carried out. Modern Islamic Boarding School El Karim Cibuah Warunggunung Lebak Banten was chosen as the location of the activity by looking at the availability of programs to be implemented which are in line with the program to strengthen literacy culture in Islamic boarding schools.